The implementation of virtual instruction in relation to x-ray anatomy and positioning in a chiropractic degree program: a descriptive paper. - Rush PO; Boone WR (Journal of Chiropractic Education (Association of Chiropractic Colleges))
This article provides information regarding the introduction of virtual education into classroom instruction, wherein a method of classroom instruction was developed with the use of a computer, digital camera, and various software programs. This approach simplified testing procedures, thus reducing institutional costs substantially by easing the demand for manpower, and seemed to improve average grade performance. Organized files with hundreds of digital pictures have created a range of instructor resources. Much of the new course materials were organized onto compact disks to complement course notes. Customizing presentations with digital technology holds potential benefits for students, instructors and the institution. (J Chiropr Educ 2009;23(1):000-000)